Elevated Corticosterone Level Due To Chronic Stress on Hb-Egf Expression as a Marker of Endometrial Receptivity Disorder in Rattus norvegicus (Indian Journal of Public Health Research & Development, 2020)
Endometrial receptivity is a physiological state in which the endometrium obtains an adhesive phenotypethat allows embryo implantation and have a role in the problem of implantation failure. Endometrialreceptivity disorders can be caused by interference with the Hypothalamus-Pituitary-Gonad (HPG) axisdue to the activation of the Hypothalamus-Pituitary-Adrenal (HPA) axis by stress. HB-EGF is a biomarkerof endometrial receptivity that plays a role in the decidualization of endometrial stromal cells to reach thereceptive state and initiation of implantation. Corticosterone is the dominant glucocorticoid hormone inrodents, as is cortisol in humans. High corticosterone due to chronic stress triggers disruption of homeostasisin the endometrium by resulting in decreased levels of HB-EGF. This study aims to find out the effectof increased corticosterone levels due to chronic stress on HB-EGF expression in endometrium Rattus norvegicus. This research has obtained ethical eligibility from the Research Ethics Commission of the Facultyof Medicine Airlangga University. The samples on this study were 34 rat (Rattus norvegicus) which weredivided into 2 groups, the control group and the stress treatment group using the Chronic Unpredictable MildStress (CUMS) method. Corticosterone level were obtain from blood serum detected via ELISA and HBEGF expression was obtained from endometrial in diestrus phase was evaluated by immunohistochemicalmethods. Corticosterone levels in the stress treatment group were higher (72.84 ± 64.03) than in the controlgroup (23.29 ± 8.42). HB-EGF expression in the stress treatment group was lower (82.06 ± 5.91) than inthe control group (118.76 ± 13.20). Statistical tests showed significant differences in HB-EGF expression inendometrium Rattus norvegicus p = 0,000 (p
Keywords: chorticosterone, chronic stress, HB-EGF expression, endometrial receptivity